Implementasi Prinsip Good Governance Dalam Mendorong Optimalisasi Layanan Publik (Tinjauan Literatur) - Sjachrawy, La Ode Muhammad Ichwan; Ikhsan, Zanuar; Laode, Ringo Taufan; Satyadharma, Maudhy; Susanti, Neni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the implementation of good governance principles in driving the optimization of public services through a literature review. The main focus is on the four key principles of transparency, accountability, participation and responsiveness which are believed to improve the quality of public services. This research uses literature study method with literature study approach and narrative model. Data were collected through analysis and comparison against various trusted sources, such as reputed international journals and related e-books. The results of the study found that the implementation of good governance principles, such as transparency, accountability, participation, and responsiveness, proved to be highly effective in encouraging the optimization of public services. The literature review of several research journals found Public Service Quality Optimization and some Supporting factors, the role of Good Governance in Improving Government Performance and Economic Growth, need for services, accountability, and barriers in the implementation of public service improvement technologies and Media requirements.